Mental Health and Wellbeing in the Anthropocene A Posthuman Inquiry - Mcphie, Jamie; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book makes the unorthodox claim that there is no such thing as mental health. It also deglamourises nature-based psychotherapies, deconstructs therapeutic landscapes and redefines mental health and wellbeing as an ecological process distributed in the environment - rather than a psychological manifestation trapped within the mind of a human subject. Traditional and contemporary philosophies are merged with new science of the mind as each chapter progressively examples a posthuman account of mental health as physically dispersed amongst things - emoji, photos, tattoos, graffiti, cities, mountains - in this precarious time labelled the Anthropocene. Utilising experimental walks, play scripts and creative research techniques, this book disrupts traditional notions of the subjective self, resulting in an Extended Body Hypothesis - a pathway for alternative narratives of human-environment relations to flourish more ethically. This transdisciplinary inquiry will appeal to anyone interested in non-classificatory accounts of mental health, particularly concerning areas of social and environmental equity - post-nature.
1. Introduction -- 2. The Material (Re)Turn-to Mental Health -- 3. The Accidental Death of Mr. Happy and the Medical Gaze -- 4. The Birth of Mr. Messy: Post-Qualitative Inquiry, Rhizoanalysis and Psychogeography -- 5. The Healing Power of Nature(s) -- 6. Agential Dancing -- 7. Extended Body Hypothesis (EBH) -- 8. Interlude: Liverpool ONE-Liverpool Too: A Therapeutic Tale of Two Cities -- 9. The Aesthetics of a Teletubby Landscape: A Short History of a Romantic Gaze -- 10. The Depression of POPS -- 11. Posthuman Therapeutic Inquiry -- 12. Conclusion: There Is No Such Thing as Mental Health.
Keywords: Human geography; Philosophy of mind; Community psychology; Psychotherapy .; Human Geography; Philosophy of Mind; Community Psychology; Psychotherapy